Examining Factors in Preventing Foodborne Diseases among Food Handlers at Military Dining Hall - Warman, Mohamad Shakir Eddy; Issa, Zuraini Mat (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aims to determine Food Safety (FS) knowledge, practice in preventing Foodborne Disease (FBD), and risk perception related to food handling among food handlers at military bases. An Optimistic Bias (OB) in preventing FBD were examined based on the risk perception responses. A set of questionnaires was sent to an officer at each military base in Malaysia. Later, the officer would conveniently distribute the questionnaire to approximately half of the targeted respondents. A total of 284 data were gathered and were analysed using SPSS version 20. The findings revealed that food handlers had good FS knowledge scores and practice to prevent FBD. However, it was found that different risk perception levels were present, indicating OB. The existence of OB was observed in all comparisons and situations except for the question about sanitising utensils. Hence, a conclusion can be made that there is a tendency that food handlers tend to neglect and overlook FS procedures, and can contaminate foods due to the presence of OB. This study will contribute significantly to military foodservice establishments in Malaysia regarding food hygiene and safety awareness.